Public administration of economic development in the context of the institutional theory - Дудченко, Валентина Віталіївна; Дудченко, В. В.; Дудченко, Валентина Витальевна; Dudchenko, Valentyna V.; Dudchenko, Valentina V.; Вітман, Костянтин Миколайович; Вітман, К. М.; Витман, Константин Николаевич; Vitman, Kostiantyn M.; Vitman, Konstantin (Baltija Publishing, 2018)
One of the priorities of socio-economic reform in Ukraine is the modernization of the structure of the national economy and its growth. An effective structure of the economy, which will correspond to a socially oriented model of economic growth and will be based on the use of both the country’s competitive advantages in the global division of labour and the economic benefits of cooperation, will guarantee the independence of any country and will be the key to its dynamic development. The development of economic theory is due to the emergence of fundamentally new ideas, sustainable accumulation of knowledge, intellectual and meaningful updating of established concepts and theories, the formation of new scientific schools. A new paradigm of economic theory should explain the real processes in real economies, which operate on the principles of complex systems of synergistic nature and the theory of nonlinear dynamics. There is a process of theoretical polystructuredness both of mainstream and heterodoxy. An important task is to form an interdisciplinary dialogue between economists and scientists, which stipulates the relevance of the research topic. The subject of the study is the theoretical and methodological foundations and approaches to state management of economic development in the context of the institutional theory. The purpose of the study is to determine the role and influence of public administration of the development of the economy in the context of institutional theory and to develop strategic goals of the state’s innovation policy. Methodology. Directions of correlation of the system of economic development of the country and the potential of the state development with the historical preconditions for the emergence and development of the institutional doctrine of economic theory are investigated. Based on the revealed interrelations, the necessity of using instruments of institutionalism for studying the economic development system is substantiated. The state, in all available ways, should encourage economic actors to develop and implement innovations, thereby creating favourable conditions for innovative and technological development of production, saturation of the domestic market with highly competitive goods and services, which, in turn, will strengthen export potential, fill the budgets of all levels, increase incomes of business entities, reduce unemployment and improve working conditions, increase social security of the population, and also strengthen the positive image of public administration and local self-government bodies. That is, the socio-economic development of the country depends directly on the innovation-technological potential and on the efficiency of public administration in its development at all levels of the economy. Conclusions. The author generalizes the theoretical and methodological foundations of the country’s development in the context of the institutional theory: the system of economic development of the state has a set of direct and indirect links with the historical background of the emergence and development of an institutional doctrine of economic theory; the revealed directions of correlation contribute to the formation of a scientific and methodological basis for further study of economic development and economic potential of a country (state) in the context of the institutional doctrine of economic theory in its relation to the public administration theory; the economic development of a country (state) depends on the institutional environment, in which it operates, and is both an object of its influence and a subject that determines its transformation. The author investigates the theoretical principles of state regulation of innovative and technological development of the country’s economy. The existing strategies and programs of innovative development and innovation activity in Ukraine are explored. The state of innovation and technology of the national economy and the potential of key sectors of the economy in terms of innovative development are analysed.

Одним із пріоритетів соціально-економічної реформи в Україні є модернізація структури національної економіки та її зростання. Ефективна структура економіки, яка відповідатиме соціально орієнтованій моделі економічного зростання і ґрунтуватиметься на використанні як конкурентних переваг країни у глобальному поділі праці, так і економічних переваг кооперації, гарантуватиме незалежність будь-якого країни і стане запорукою її динамічного розвитку. Розвиток економічної теорії зумовлений появою принципово нових ідей, стійким накопиченням знань, інтелектуальним і змістовним оновленням усталених концепцій і теорій, формуванням нових наукових шкіл. Нова парадигма економічної теорії має пояснювати реальні процеси в реальній економіці, які функціонують на принципах складних систем синергетичного характеру та теорії нелінійної динаміки. Відбувається процес теоретичної поліструктурності як мейнстріму, так і гетеродокси. Важливим завданням є формування міждисциплінарного діалогу між економістами та науковцями, що обумовлює актуальність теми дослідження. Предметом дослідження є теоретико-методологічні основи та підходи до державного управління економічним розвитком у контексті інституційної теорії. Метою дослідження є визначення ролі та впливу державного управління на розвиток економіки в контексті інституційної теорії та розробка стратегічних цілей інноваційної політики держави. Методологія. Досліджено напрями співвідношення системи економічного розвитку країни та потенціалу розвитку держави з історичними передумовами виникнення та розвитку інституційної доктрини економічної теорії. На основі виявлених взаємозв'язків обґрунтовано необхідність використання інструментів інституціоналізму для вивчення системи економічного розвитку. Держава всіма доступними способами повинна заохочувати суб'єктів економіки до розробки та впровадження інновацій, створюючи тим самим сприятливі умови для інноваційно-технологічного розвитку виробництва, насичення внутрішнього ринку висококонкурентоспроможними товарами та послугами, що, у свою чергу, посилить експортний потенціал, наповнення бюджетів усіх рівнів, збільшення доходів суб’єктів підприємницької діяльності, зниження рівня безробіття та покращення умов праці, підвищення соціальної захищеності населення, а також зміцнення позитивного іміджу органів державного управління та місцевого самоврядування. Тобто соціально-економічний розвиток країни безпосередньо залежить від інноваційно-технологічного потенціалу та від ефективності державного управління в його розвитку на всіх рівнях економіки. Висновки. Автор узагальнює теоретико-методологічні засади розвитку країни в контексті інституційної теорії: система економічного розвитку держави має сукупність прямих і опосередкованих зв’язків з історичними передумовами виникнення та розвитку інституційної доктрини економічної теорії; виявлені напрями співвідношення сприяють формуванню науково-методологічної бази для подальшого вивчення економічного розвитку та економічного потенціалу країни (держави) у контексті інституційної доктрини економічної теорії у її співвідношенні з теорією державного управління; економічний розвиток країни (держави) залежить від інституційного середовища, в якому вона діє, і є одночасно об'єктом її впливу і суб'єктом, що визначає її трансформацію. Досліджено теоретичні засади державного регулювання інноваційно-технологічного розвитку економіки країни. Досліджено існуючі стратегії та програми інноваційного розвитку та інноваційної діяльності в Україні. Проаналізовано інноваційно-технологічний стан національної економіки та потенціал ключових галузей економіки в умовах інноваційного розвитку.
Dudchenko V. Public administration of economic development in the context of the institutional theory / V. Dudchenko, K. Vitman // Baltic Journal of Economic Studies. - Vol. 4. - No. 1. - Baltija Publishing, 2018. - P. 139-147.
Keywords: institutional doctrine; public administration; stimulation mechanism; innovative and technological development; state regulation; innovation strategy; інституційна доктрина; державне управління; механізм стимулювання; інноваційно-технологічний розвиток; державне регулювання; інноваційна стратегія; Research Subject Categories::LAW/JURISPRUDENCE